Does the dose-solubility ratio affect the mean dissolution time of drugs? - Lánský, P; Weiss, M (Pharmaceutical research, 1999)
PURPOSE: To present a new model for describing drug dissolution. On the basis of the new model to characterize the dissolution profile by the distribution function of the random dissolution time of a drug molecule, which generalizes the classical first order model. METHODS: Instead of assuming a constant fractional dissolution rate, as in the classical model, it is considered that the fractional dissolution rate is a decreasing function of the dissolved amount controlled by the dose-solubility ratio. The differential equation derived from this assumption is solved and the distribution measures (half-dissolution time, mean dissolution time, relative dispersion of the dissolution time, dissolution time density, and fractional dissolution rate) are calculated. Finally, instead of monotonically decreasing the fractional dissolution rate, a generalization resulting in zero dissolution rate at time origin is introduced. RESULTS: The behavior of the model is divided into two regions defined by q, the ratio of the dose to the solubility level: q < 1 (complete dissolution of the dose, dissolution time) and q > 1 (saturation of the solution, saturation time). The singular case q = 1 is also treated and in this situation the mean as well as the relative dispersion of the dissolution time increase to infinity. The model was successfully fitted to data (1). CONCLUSIONS: This empirical model is descriptive without detailed physical reasoning behind its derivation. According to the model, the mean dissolution time is affected by the dose-solubility ratio. Although this prediction appears to be in accordance with preliminary application, further validation based on more suitable experimental data is required.
Keywords: Models, Chemical; Pharmaceutical Preparations; tobolky; Dose-Response Relationship, Drug; chemické modely; vztah mezi dávkou a účinkem léčiva; léčivé přípravky; Solubility; Water; Capsules; rozpustnost; voda